A sulfonium tethered peptide ligand rapidly and selectively modifies protein cysteine in vicinity. Issue 19 (17th April 2019) - Wang, Dongyuan; Yu, Mengying; Liu, Na; Lian, Chenshan; Hou, Zhanfeng; Wang, Rui; Zhao, Rongtong; Li, Wenjun; Jiang, Yixiang; Shi, Xiaodong; Li, Shuiming; Yin, Feng; et al.
Abstract : A unique peptide stabilization method provides a tethered sulfonium that can rapidly and selectively modify protein cysteine in close vicinity. Abstract : Significant efforts have been invested to develop site-specific protein modification methodologies in the past two decades. In most cases, a reactive moiety was installed onto ligands with the sole purpose of reacting with specific residues in proteins. Herein, we report a unique peptide macrocyclization method via the bis-alkylation between methionine and cysteine to generate cyclic peptides with significantly enhanced stability and cellular uptake. Notably, when the cyclized peptide ligand selectively recognizes its protein target with a proximate cysteine, a rapid nucleophilic substitution could occur between the protein Cys and the sulfonium center on the peptide to form a conjugate. The conjugation reaction is rapid, facile and selective, triggered solely by proximity. The high target specificity is further proved in cell lysate and hints at its further application in activity based protein profiling. This method enhances the peptide's biophysical properties and generates a selective ligand-directed reactive site for protein modification and fulfills multiple purposes by one modification. This proof-of-concept study reveals its potential for further broad biological applications.